Pengaruh Self Leadership dan Semangat Kerja terhadap Kinerja Karyawan pada PT BPR Wahyu Nirmala di Mengwi Badung (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study is to determine the partial and simultaneous influence of self-leadership and morale variables on employee performance. The location of this study was conducted at PT. BPR Wahyu Nirmala in Mengwi Badung where the population and sample are all employees totaling 34 respondents, where the sample determination method uses saturated samples. The analysis technique used is multiple linear regression analysis. The results of this study were found that 1) Self leadership has a positive and partially significant effect on employee performance. 2) Morale has a positive and partially significant effect on employee performance. 3) Self-leadership and morale have a simultaneous positive and significant effect on employee performance at PT BPR Wahyu Nirmala di Mengwi Badung. Advice that can be given for employees to work on time, motivate themselves, and set strict sanctions for all employees.